Increasing Students' Learning Interest by Using Question Cards to Create Islamic Cultural History Learning Media - A. Sulaeman; Makhrus Makhrus; Ibnu Hasan; Makhful Makhful (CV. Creative Tugu Pena, 2026)
The development of Islamic cultural history learning media is very important to increase students' interest in learning. This type of research is field research with a descriptive qualitative approach with data collection techniques through observation, documentation, and interviews, while the analysis of the data obtained is presented descriptively, both in writing and direct observation, then the data is reduced by making abstractions and arranged in the form of units, details, data checks to avoid invalidity. The results of this study indicate that the use of learning media in the subject of Islamic cultural history is carried out using spin media-based question cards which provide convenience to teachers in compiling learning materials because of its use through Microsoft Office Power Point. The stages in its implementation are teachers preparing materials that have been arranged into Spin media, teachers carrying out the learning process which includes preliminary activities, core activities, closing activities. The advantages of applying question cards in Islamic cultural history learning as a form of teacher innovation, interactive communication, and students' enthusiasm in participating in learning. Meanwhile, related to the disadvantages of question cards, it requires proper time management and requires supporting facilities and infrastructure